Supporting and financing creativity and innovation in small and medium enterprises Algeria case study - maiza, messaoud amir (Journal of Research in Finance and Accounting, 2022)
Through this research paper, we aim to determine whether Algeria has the necessary laws, legislation and institutions to support and finance creativity and innovation in SMEs. To achieve this goal, we used the descriptive analytical method to describe and analyze data and information published in the Organization for Economic Cooperation and Development reports. Through this study, we concluded that Algeria does not have an effective institutions to support innovation and creativity in business organizations, except for some contributions such as the establishment of research project units in the Ministry of Higher Education and Scientific Research in partnership with economic operators, which may be considered insufficient and not significantly influential in supporting creativity and innovation in the SMEs in Algeria.